Gαq and Phospholipase Cβ signaling regulate nociceptor sensitivity in Drosophila melanogaster larvae - Joshua A. Herman; Adam B. Willits; Andrew Bellemer (PeerJ, 2018)
Drosophila melanogaster larvae detect noxious thermal and mechanical stimuli in their environment using polymodal nociceptor neurons whose dendrites tile the larval body wall. Activation of these nociceptors by potentially tissue-damaging stimuli elicits a stereotyped escape locomotion response. The cellular and molecular mechanisms that regulate nociceptor function are increasingly well understood, but gaps remain in our knowledge of the broad mechanisms that control nociceptor sensitivity. In this study, we use cell-specific knockdown and overexpression to show that nociceptor sensitivity to noxious thermal and mechanical stimuli is correlated with levels of Gαq and phospholipase Cβ signaling. Genetic manipulation of these signaling mechanisms does not result in changes in nociceptor morphology, suggesting that changes in nociceptor function do not arise from changes in nociceptor development, but instead from changes in nociceptor activity. These results demonstrate roles for Gαq and phospholipase Cβ signaling in facilitating the basal sensitivity of the larval nociceptors to noxious thermal and mechanical stimuli and suggest future studies to investigate how these signaling mechanisms may participate in neuromodulation of sensory function.